2014
DOI: 10.1039/c4fo00478g
|View full text |Cite
|
Sign up to set email alerts
|

Bi-compartmental elderly or adult dynamic digestion models applied to interrogate protein digestibility

Abstract: The world's population is inevitably ageing thanks to modern progress; however, the development of food and oral formulations tailored to the needs of the elderly is still in its infancy. In vitro digestion models offer high throughput, robust and practically ethics free evaluation of the digestive fate of ingested products. To date, no data have been made publicly available to facilitate the development or application of an in vitro model mirroring the physicochemical conditions of the elderly gastrointestina… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
39
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
4
2
2

Relationship

1
7

Authors

Journals

citations
Cited by 73 publications
(41 citation statements)
references
References 37 publications
2
39
0
Order By: Relevance
“…absorption and diffusion) and rheological aspects (i.e. mixing) (Blanquet et al, 2004;Dekkers, Kolodziejczyk, Acquistapace, Engmann, & Wooster, 2016;Kong & Singh, 2010a;Levi & Lesmes, 2014;Mercuri, Lo Curto, Wickham, Craig, & Barker, 2008;Shani-Levi, Levi-Tal, & Lesmes, 2013;Tharakan, Norton, Fryer, & Bakalis, 2010;Yoo & Chen, 2006). To date, both advanced and simple IVD models have be used to investigate a variety of systems.…”
Section: Current Status Of Adult In Vitro Digestion (Ivd) Modelsmentioning
confidence: 99%
See 2 more Smart Citations
“…absorption and diffusion) and rheological aspects (i.e. mixing) (Blanquet et al, 2004;Dekkers, Kolodziejczyk, Acquistapace, Engmann, & Wooster, 2016;Kong & Singh, 2010a;Levi & Lesmes, 2014;Mercuri, Lo Curto, Wickham, Craig, & Barker, 2008;Shani-Levi, Levi-Tal, & Lesmes, 2013;Tharakan, Norton, Fryer, & Bakalis, 2010;Yoo & Chen, 2006). To date, both advanced and simple IVD models have be used to investigate a variety of systems.…”
Section: Current Status Of Adult In Vitro Digestion (Ivd) Modelsmentioning
confidence: 99%
“…However, the target population of the study focused solely on women in the ages of 50e70. In relation to IVD models recreating elderly digestive conditions, two recent studies have been identified to apply in vivo data to the modelling parameters (Denis et al, 2016;Levi & Lesmes, 2014). The first reports the set-up of a dynamic gastro-intestinal elderly (>70 years old) model based on commercial bioreactors with details on all the parameters used and the rationale of their selection (Levi & Lesmes, 2014).…”
Section: Elderlymentioning
confidence: 99%
See 1 more Smart Citation
“…As interest in research involving simulating digestion continues to grow, efforts are being made to validate the methods used against in vivo data (Bornhorst, Roman, Dreschler, & Singh, 2014). In addition, efforts are being made to extend the research to other more specific groups such as infants (de Oliveira et al, 2016) or the elderly (Levi & Lesmes, 2014). Given the amount of research that is going on around Europe, it is clear that in the near future there will be papers showing the extent to which in vitro methods such as the Infogest static model can be used to predict in vivo outcomes.…”
Section: Introduction To the Special Issuementioning
confidence: 99%
“…Moreover, the aging of the population raises new challenges. The elderly are more vulnerable to nutritional deficiencies, due to reduced appetite, higher prevalence of chronic diseases, as well as changes in the gastrointestinal function (Salles 2007;Levi and Lesmes 2014).…”
Section: Qi Luomentioning
confidence: 99%